Peran Katekis dalam Tantangan Karya Katekese Digital - Chechilia A. Banjarnahor; Intansakti Pius X (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
Keywords: Role of the Catechist; Challenge; Digital Catechesis This research aims to find the role of catechists in the challenge of digital catechesis. In PKKI X, this awareness can be seen in the form of communication in catechesis finding new ways, namely digital communication. The Church sees the digital era, not only in terms of opportunities in terms of new ways of catechesis, but the Church also remains alert to the challenges in digital catechesis. These challenges certainly have a negative impact on the life of faith. Modern developments in the digital world have made humans experience memory loss or amnesia. Today's humans live in an all-digital era, making themselves dominated by technological networks. Modern humans only consist of flesh, bodies and machines, this is what makes them wrong. Humans actually have spiritual power. In order to restore people's memory of their identity as human beings who are noble and have spirituality, catechesis becomes a learning process to become more human. The Church must play an active role in the challenge of digital catechesis. So that negative impacts in the life of faith can be reduced and handled well, all lines in the Church must be involved in responding to this challenge, including a catechist. The catechist is the spearhead of the people, because the catechist understands the real situation that the people are experiencing. The challenges of digital catechesis influence the work of catechesis for the people. In the era of digital catechesis, catechists need to be involved and take a role in facing challenges in digital catechesis. This research is included in qualitative research with documentation methods. Data collection in this research was by finding data in documents related to the theme. After the data is collected, the next step is analyzing the data and interpreting the data. Based on the research results, it was found that in facing the challenges of digital catechesis, three important roles were found in a catechist. These roles are in the form of; a catechist must be able to master digital, the catechist becomes a facilitator who leads the people to an encounter with God, and the catechist becomes a partner of the Imams in the work of digital catechesis. This role is where a catechist should carry out his duties in the challenges of digital catechesis.